Epidemiology and Clinical Outcomes of Hospitalizations for Acute Respiratory or Febrile Illness and Laboratory-Confirmed Influenza Among Pregnant Women During Six Influenza Seasons, 2010–2016. (26th December 2019) - Dawood, Fatimah S; Garg, Shikha; Fink, Rebecca V; Russell, Margaret L; Regan, Annette K; Katz, Mark A; Booth, Stephanie; Chung, Hannah; Klein, Nicola P; Kwong, Jeffrey C; Levy, Avram; Naleway, Allison; et al.
Abstract: Background: Pregnant women are at increased risk of seasonal influenza hospitalizations, but data about the epidemiology of severe influenza among pregnant women remain largely limited to pandemics. Methods: To describe the epidemiology of hospitalizations for acute respiratory infection or febrile illness (ARFI) and influenza-associated ARFI among pregnant women, administrative and electronic health record data were analyzed from retrospective cohorts of pregnant women hospitalized with ARFI who had testing for influenza viruses by reverse-transcription polymerase chain reaction (RT-PCR) in Australia, Canada, Israel, and the United States during 2010–2016. Results: Of 18 048 ARFI-coded hospitalizations, 1064 (6%) included RT-PCR testing for influenza viruses, 614 (58%) of which were influenza positive. Of 614 influenza-positive ARFI hospitalizations, 35% were in women with low socioeconomic status, 20% with underlying conditions, and 67% in their third trimesters. The median length of influenza-positive hospitalizations was 2 days (interquartile range, 1–4), 18% (95% confidence interval [CI], 15%–21%) resulted in delivery, 10% (95% CI, 8%–12%) included a pneumonia diagnosis, 5% (95% CI, 3%–6%) required intensive care, 2% (95% CI, 1%–3%) included a sepsis diagnosis, and <1% (95% CI, 0%–1%) resulted in respiratory failure. Conclusions: Our findings characterize seasonal influenza hospitalizations among pregnant women and can inform assessments of the public health and economic impact of seasonal influenza on pregnant women. Abstract : Among influenza-positive hospitalizations for acute respiratory or febrile illness, 80% occurred in previously healthy women without underlying medical conditions, and the majority occurred in women in their third trimesters. Most hospitalized women were not vaccinated against influenza.